Measurement and Analysis with KPIs based on an AMI system - Javier Rosero Garcia; Kevin Morgado; Álvaro Zambrano (IAES Indonesian Section, 2022)
This paper presents the development of a series of key performance indicators (KPI´s) for the electrical system of the campus of the National University of Colombia based on the deployed smart metering infrastructure (AMI). In order to develop the proposed indicators, it was necessary to use different sources of information to complement the data provided by the AMI system. For each of the proposed indicators is presented the way in which each selected indicator is calculated, and an analysis of the behavior obtained for each KPI. It was possible to observe how, based on the results obtained from the different indicators proposed, periods of inefficiency in terms of electricity consumption were identified. Finally, the conclusions obtained during the development of the project are presented.